Ownership of the wreck of the R.M.S. Titanic. A Private International Law analysis - Carrascosa González, Javier (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
The purpose of this study is to explore the private international law rules of the United Kingdom, the United States of America and Spain with regard to the ownership of the wreck of the H.M.S. TITANIC. The analysis of the not very useful international legal instruments which deal with the ownership of the assets is more than disappointing, lacking Private Law solutions. This work defends that the ownership of the TITANIC should be attributed to the person who can best rescue the goods from the wreck and expose them to all of Humanity. From this perspective, it is North American private international law that is most competitive, as ownership is attributed to the salvor of the assets found in the Titanic wreck.